2021
DOI: 10.1039/d1ra01793d
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion size profoundly affects H3glyox chelate chemistry

Abstract: The bisoxine hexadentate chelating ligand, H3glyox was investigated for its affinity for Mn2+, Cu2+ and Lu3+ ions; all three metal ions are relevant with applications in nuclear medicine and medicinal inorganic chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, H 2 pyhox proved to be suitable for 225 Ac III [112]. Smaller radiometal ions such as 44 Sc III , 68 Ga III and 111 In III are efficiently complexed with H 3 glyox, a ligand containing glycine and oxine donor groups [113]. This ligand shows interesting fluorescence properties after the addition of metal ions and is thus a promising system for nuclear/optical imaging [114].…”
Section: Mixed Ligand Systemsmentioning
confidence: 99%
“…Furthermore, H 2 pyhox proved to be suitable for 225 Ac III [112]. Smaller radiometal ions such as 44 Sc III , 68 Ga III and 111 In III are efficiently complexed with H 3 glyox, a ligand containing glycine and oxine donor groups [113]. This ligand shows interesting fluorescence properties after the addition of metal ions and is thus a promising system for nuclear/optical imaging [114].…”
Section: Mixed Ligand Systemsmentioning
confidence: 99%
“…Advantages and disadvantages of macrocyclic DOTA, NOTA, and their related chelating groups, DOTAGA, α-(2-carboxyethyl)-1,4,7,10 tetraazacyclododecane-1,4,7,10-tetraaceticacid, NOTAGA, 1,4,7-triazacyclononane-1-glutaric acid-4,7-acetic acid, , etc., have been reviewed. In addition, series of acyclic chelators, DTPA, HBED, AAZTA, etc., , have been reported. Many DOTA and DTPA derivatives have been successfully developed in recent years as new chelating agents by which forming stable metal complexes with enhanced properties for radiopharmaceuticals. ,, Originally, AAZTA (6-amino-6-methylperhydro-1,4-diazepinetetraacetic acid), a heptadentate chelator, was first reported by Aime et al designed to form gadolinium (Gd) complexes as MRI contrast imaging agents. It was reported that AAZTA is also a promising chelator for gallium-68 or scandium-44. , Promising AAZTA-based bifunctional chelators for preparation of analogs of [ 68 Ga]­Ga-DOTA-TOC (NETSOPT), [ 68 Ga/ 44 Sc/ 177 Lu]­Ga/Sc/Lu-AAZTA-TOC. , as well as [ 68 Ga]­Ga-AAZTA-PSMA derivatives were prepared and evaluated.…”
Section: Introductionmentioning
confidence: 99%